Badiou's theory of the event and the politics of trauma recovery. (December 2014) - Bistoen, Gregory; Vanheule, Stijn; Craps, Stef
There exists a conceptual parallel between psychological accounts of psychic trauma on the one hand, and French philosopher Alain Badiou's notion of the event on the other: both are defined by a relation of incommensurability or excessiveness with regard to the pre-existent context or system. Further development of this parallel, i.e., viewing trauma as an event in the Badiouian sense, enables us to pinpoint and clarify a logical fallacy at work in psychological theories of post-traumatic growth. By thinking of trauma recovery as a process of accommodating the pre-existent mental schemata to the "new trauma-related information, " these theories risk taking as a given that which must first be constituted by the subject: the "content" (i.e., "information") of the trauma. By emphasizing the necessity of the activity of the subject for the development of a new context that allows the event to be "read, " Badiou's theory of the subject offers a way around the aforementioned logical fallacy. In so doing, it re-introduces the essential yet generally neglected political dimension of trauma recovery. This is illustrated through the example of the speak-outs of the 1970s women's liberation movement.